Optimization of speech codecs on set of indicators of quality - Bezruk, Valery; Skorik, Yulia (Видавництво Львівської політехніки, 2010)
In article theoretical and practical features of application of methods multicriteria optimisation for a choice of optimum speech codecs taking into account set of indicators of quality are considered.
Keywords: optimisation; indicators of quality; the speech codec; IP-telephony